2023
DOI: 10.1039/d3ta01668d
|View full text |Cite
|
Sign up to set email alerts
|

Revealing surface fine structure on PtAu catalysts by anin situATR-SEIRAS CO-probe method

Abstract: The electrochemical performance of Pt-based catalysts depend on their surface structure. Nevertheless, it is still a challenge to investigate their intricate surface active sites. Here, PtAu films were utilized as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…By applying an electrode potential of 0.2 V to facilitate CO adsorption on the Fe site (Supplementary Fig. 10), infrared vibrational frequency data were acquired within the range of ν = 1950~2050 cm -1 , corresponding to the adsorption of monocarboxylic ligands on the Fe site 41,42 . The obtained data demonstrated that the νCO values exhibited an increase proportional to the degree of polymerization (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…By applying an electrode potential of 0.2 V to facilitate CO adsorption on the Fe site (Supplementary Fig. 10), infrared vibrational frequency data were acquired within the range of ν = 1950~2050 cm -1 , corresponding to the adsorption of monocarboxylic ligands on the Fe site 41,42 . The obtained data demonstrated that the νCO values exhibited an increase proportional to the degree of polymerization (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The structure and characterization of electrochemical IR cells have been described in previous work . The plating solution was 0.03 M HAuCl 4 + 0.3 M Na 2 SO 3 + 0.1 M Na 2 S 2 O 3 5H 2 O + 0.1 M NH 4 Cl.…”
Section: Methodsmentioning
confidence: 99%
“…The structure and characterization of electrochemical IR cells have been described in previous work. 24 The plating solution was 0.03 M HAuCl 4 + 0.3 M Na 2 SO 3 + 0.1 M Na 2 S 2 O 3 5H 2 O + 0.1 M NH 4 Cl. The secondary chemical gold plating of silicon prisms/ silicon wafers is described in detail in previous reports: The prisms/silicon wafers were milled with 1, 0.3, and 0.05 μm Al 2 O 3 , and ultrasonic cleaning was done with water and acetone.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…[1][2][3][4] Lithium ion batteries (LIBs) have evolved into a fundamental component of modern society, energizing a wide array of consumer electronics, including laptops, cellphones, and more. [5][6][7] Recently, the increasing demands for electric vehicles and energy storage systems have significantly elevated the cost of lithium salts. [8][9][10] Additionally, the new emerging applications usually require battery technologies characterized by low cost and high energy density.…”
Section: Introductionmentioning
confidence: 99%